2015
DOI: 10.1037/a0038754
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy-based modulations of lag-1 sparing and extended sparing during the attentional blink.

Abstract: Over 20 years of research has shown that impairments in the identification of sequential targets—known as the attentional blink—are often eliminated when 2 or more targets are presented in direct succession. Such instances of lag-1 sparing and, more recently, extended sparing are widely attributed to the fact that directly successive visual inputs that possess common characteristics can be processed during an extended attentional window. Critically, this explanation implies that direct temporal succession and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 82 publications
(203 reference statements)
7
14
0
Order By: Relevance
“…The one exception was the item at Lag 1, where the reported orientation of T1 was as strongly influenced by the orientation of T2 as by the orientation of T1. This observation is in line with numerous studies which have suggested that temporal order information can be lost for consecutive targets 29,33 . This phenomenon, also known as Lag 1 switching, where the perceived order of the targets is reversed, explains why the accuracy of orientation judgements on both T1 and T2 was reduced at Lag 1 (see also Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The one exception was the item at Lag 1, where the reported orientation of T1 was as strongly influenced by the orientation of T2 as by the orientation of T1. This observation is in line with numerous studies which have suggested that temporal order information can be lost for consecutive targets 29,33 . This phenomenon, also known as Lag 1 switching, where the perceived order of the targets is reversed, explains why the accuracy of orientation judgements on both T1 and T2 was reduced at Lag 1 (see also Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
“…Experiment 1-biased perception of targets by preceding distractors. Previous work suggests that distractor processing can significantly interfere with target processing [39][40][41] , particularly for the immediate post-target item which can be integrated into the target representation 28,29,33 . To determine whether this was the case in our data, we repeated the previous analysis but used the difference in orientation between the target and each of the other items in the RSVP stream ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The one exception was the item at Lag 1, where the reported orientation of T1 was as strongly influenced by the orientation of T2 as by the orientation of T1. This observation is in line with numerous studies which have suggested that temporal order information can be lost for consecutive targets 25, 26, 30 . This phenomenon, also known as Lag 1 switching, where the perceived order of the targets is reversed, explains why the accuracy of orientation judgements on both T1 and T2 was reduced at Lag 1 (see also Supplementary Figure 4).…”
Section: Resultssupporting
confidence: 92%
“…This finding is not explicitly predicted by any existing account of the AB. The largest bias was for Lag 1 trials, in which the two targets appear sequentially, a result that is consistent with Lag 1 switching 25, 26, 30 . The orientation of the immediate post-target distractor also significantly biased the perceived target orientation, whereas the distractors that appeared between the targets did not bias perceptual judgements.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation